(3TQM fXe GdYhGed GdeFIs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg, CeG(B: (3cdeI ajgG eYfi GdTQW adPdc cGfJ dGReI dgG s
(3BNQgG (B:s
(3dCf EgGfI Gdehdi ef dhGRe VQH GdZdGe hgPG HGH ddEWfGH ajg eMGd, dcfg jaVj Edi GdedGd, hGbJUQJ Ydi gPG GdbOQ s
(3JYGhQ YdjgG fGSNGf hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs